Testing the Hypothesis of the Triple Deficit in the Egyptian Economy Using Nonlinear Autoregressive Distributed Lags - Ahmed, Ashraf (The Arab Journal of Administration, 2022)
This study aims to test the Triple Deficits hypothesis in the Egyptian economy from 1983 to 2017, using the Nonlinear Autoregressive Distributed Lags (NARDL) developed by Shin et al (2014), a research contribution that keeps pace with studies that began. The scientific community around the world is preoccupied with reformulating economic theories using more efficient standard techniques, and in this paper it is useful to test the hypothesis of the non-linear relationship between the savings deficit - private investment, public budget deficits (government savings) and current account deficits. The study concluded that there is a long-term cointegration relationship between the variables in study, and that the relationship between the current account deficit and both the private savings balance & the government savings balance is symmetric in the long term. The results show the significance of the private and government savings deficits, Increasing them by 1% leads to an increase in the current account deficit by 0.49 and 0.58, respectively, which is consistent with the study hypothesis, whereas a 1% decrease leads to an increase in the current account deficit by 0.56 and 0.55, respectively, and may be due This is due to the freezing of the greater part of private and government savings or not directing them to investment activities that contribute to the decrease in the current account deficit. The ECM results suggest that short-term errors can be corrected to return to long-term equilibrium, at -0.83, so any short-term shock will be corrected in about 14 months (almost 1.2 years).